Pemeringkatan Kinerja Dosen pada Perguruan Tinggi Swasta Menggunakan Algoritma Simple Additive Weighting - Mufida, Elly; Iriadi, Nandang; Andriansyah, Doni (UIN Sunan Kalijaga Yogyakarta, 2024)
The Tri Dharma of Higher Education is an obligation for lecturers while carrying out their duties as lecturers at higher education institutions, the implementation of which is regulated in Law Number 20 of 2003 concerning the National Education System. The Tri Dharma of Higher Education is a lecturer's obligation, including Education and Teaching, Research and Development, and Community Service. Lecturers need Support and motivation to implement quality Tri Dharma, especially at